Development and Evaluation of Cost of Production of Instant Chicken Soup Mix Incorporated with Spent Hen Meat Shred - Sarkar, B. K.; Upadhyay, S.; Gogoi, P.; Das, A.; Hazarika , M.; Rahman, Z. (International Journal of Livestock Research, 2019)
A study was undertaken to develop an ‘instant chicken soup mix’ incorporated with spent hen meat shred and to evaluate its cost of production. Four treatment soup mix combinations containing 0%, 20%, 25% and 30% meat shred were prepared and cost of production was evaluated. Cost of formulation was found to be highest for Treatment D followed by C, B and A. Net profit was found to be highest for Treatment D followed by C, B and A. Estimating the details of economics of the developed products, it can be concluded that a viable enterprise can be established by keeping the cost per kg as Rs. 273, Rs. 455, Rs. 500 and Rs. 546 for Treatment A, B, C and D respectively.